Regulations on Zadruga Enacted after Introduction of Serbian Civil Code in 1844 - Kulauzov, Maša (Zbornik radova Pravnog fakulteta u Novom Sadu, 2013)
Regulations on so – called zadruga (extended family, common among South Slavs) enacted after introduction of Serbian Civil Code in 1844, are examined in this paper. As zadruga was a dominant family structure in Serbia throughout XIX century, various rules regarding all important aspects of life in extended families were passed. Having in mind widespread existence and durability of zadrugas, significance of these regulations is emphasized in the article. Therefore, numerous provisions regulating legal nature of zadruga, property rights of zadruga᾿s members, rights of succession of female children and divisions of zadrugas are scrutinized and critically analyzed. The author also indicates all major changes of traditional, customary law nature of zadruga that had taken place in legislation on zadruga’s aiming to preserve extended families in considerably different social circumstances of XIX century.